Role of transcriptomics in the study of oral cancer - Prabhu Manickam Natarajan; Vidhya Rekha Umapathy (Frontiers in Oral Health)
Oral cancer, a formidable public health challenge, demands innovative approaches for early detection and effective treatment. This review explores the transformative role of transcriptomics in oral cancer research, leveraging cutting-edge technologies to decode the RNA landscape of tumors. We delve into RNA sequencing (RNA-seq), single-cell RNA sequencing (scRNA-seq), long non-coding RNA sequencing (lncRNA-seq), microarray analysis, and small RNA profiling, showcasing their unique contributions to unraveling the complexities of oral cancer. By mapping gene expression patterns, identifying biomarkers, and understanding tumor heterogeneity at an unprecedented resolution, transcriptomics offers powerful insights into the molecular mechanisms driving oral cancer. Furthermore, we highlight how these approaches pave the way for personalized medicine, enabling precise therapeutic interventions and innovative treatment strategies. The review also addresses the future directions and challenges in the field, emphasizing the need for advanced computational tools and interdisciplinary collaboration to fully harness the potential of transcriptomics in transforming oral cancer care.